Identification of Salmonella sp Bacteria in Processed Balado Shrimp Sold in Food Stalls Around Mulyosari Area - Mustofa, Nabila Amelia; Sari, Yeti Eka Sispita; Artanti, Dita; Kartikorini, Nastiti (LPPM STIKes Muhammadiyah Ciamis, 2024)
Background & Objective: Food quality is an issue of great concern in developing countries. Because many nutrients are obtained through food. Balado shrimp is a typical Padang dish with a spicy, sweet and savoury taste that is widely admired by all ages from children to adults. The presence of pathogenic bacteria, one of which is Salmonella sp, which contaminates balado shrimp food can cause health problems in the human body until death. The purpose of this study was to determine the presence or absence of Salmonella sp bacteria in processed shrimp balado sold in food stalls in the Mulyosari area. Method: In this study use as many as 30 samples of shrimp balado sold in food stalls Mulyosari area. This sample examination uses a streaking plate procedure and IMViC test. Data analysis using descriptive qualitative. Result: The results of this study showed that there were 3 samples identified Salmonella sp. Of the 30 samples, there was a range of 10% contaminated with Salmonella sp bacteria and 90% were not contaminated with Salmonella sp bacteria. Conclusion: This indicates that positive samples of balado shrimp must be further examined to determine the feasibility of consumption.